Contemporary Management of Patent Foramen Ovale: A Multinational Survey on Cardiologists' Perspective. (11th September 2021) - Dębski, Maciej; Abdelrahman, Amr; Alshehri, Halia; Prince, Marloe; Wiper, Andrew; Chalil, Shajil; Dudek, Dariusz; White, Christopher J.; Hildick-Smith, David; H. Roberts, David
Abstract : Objectives . The purpose of our survey is to analyze the clinical approach used by interventional and imaging cardiologists to diagnose, treat, and follow-up patients with PFO-related left circulation thromboembolism in different parts of the world with particular emphasis on adherence to current guidelines. Background . Firm guidelines do not cover many aspects of PFO-related patient care. Consequently, very disparate approaches exist among clinicians in the real-world. Methods . A 24-item electronic questionnaire was sent directly to experienced cardiology specialists practicing at consultant/attending positions directly involved in PFO closure management in the United States, United Kingdom, Gulf countries, and other countries. There were no unanswered questions. Responses were recorded between October 2019 and July 2020. Results . Seventy-one responses were obtained: 31 from the UK, 19 from the US, 16 from Gulf countries, 2 from Poland, and 1 response from Australia, Italy, and Switzerland. The overall response rate was 76%. Significant differences between regions were noted in the duration of ECG monitoring during the diagnostic process, PFO closure for left circulation thromboembolism other than stroke/transient ischemic attack, and intraoperative use of intracardiac echocardiography. A similar pattern was noted in the lack of routine screening for thrombophilia and the use of the long-term single antiplatelet therapy. Conclusions . The study shows a vast spectrum of opinions on the optimal approach to PFO closure with significant differences between the US, UK, and Gulf countries. The results stress the need for systematic, high-quality data on the diagnostic work-up and follow-up strategies to inform the standardized approach.